If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4s + -10 = s + 11 Reorder the terms: -10 + 4s = s + 11 Reorder the terms: -10 + 4s = 11 + s Solving -10 + 4s = 11 + s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-1s' to each side of the equation. -10 + 4s + -1s = 11 + s + -1s Combine like terms: 4s + -1s = 3s -10 + 3s = 11 + s + -1s Combine like terms: s + -1s = 0 -10 + 3s = 11 + 0 -10 + 3s = 11 Add '10' to each side of the equation. -10 + 10 + 3s = 11 + 10 Combine like terms: -10 + 10 = 0 0 + 3s = 11 + 10 3s = 11 + 10 Combine like terms: 11 + 10 = 21 3s = 21 Divide each side by '3'. s = 7 Simplifying s = 7
| 3(12-x)=4+5X | | (-2)-9=-11 | | 10n+n^2=72 | | 12-1/3x=18 | | -5x+3=2x+17 | | 6(6)=17 | | 12-(163/15) | | p-4px/p | | 4n+2n=12 | | 3=p+3-1 | | 13b-9=4b-63 | | -18n-30n=-18-10n | | 4=2x-3y | | -17=6b-7+8 | | 5x+2x-14=28 | | 2(x+2)=x-7 | | 1/3*2-4 | | -10=8b+8-5b | | 6+4n+5=-13 | | 1+4n+5=2 | | b/3-4 | | 18n-30n=-18-10n | | 1/3x0 | | 6x+5x-4x-5=23 | | 10=k+2-2k | | 3x+2(x-5)=c+6 | | 9=2n+n | | 2(x-4)+x=4x+5 | | n-3+8=4 | | -7n+7-7=21 | | -7x-3x=0 | | 15=-n+6n |